Generation Z and Entrepreneurship: Understanding the Character of Entrepreneurs in the Midst of Industrial Revolution 5.0 - Sudaryanto, Muhammad Adam; Sylvana, Andi (Universitas Pahlawan Tuanku Tambusai, 2024)
Entrepreneurship plays an important role in fostering the economy. This research aims to understand the entrepreneurial character among Generation Z in the midst of the 5.0 Industrial Revolution. This study aims to provide deeper insights into how Generation Z can contribute to sustainable innovations and economic and social progress in the era of the 5.0 Industrial Revolution by understanding their entrepreneurial characteristics. The method used in this research is quantitative descriptive through surveys. This method allows researchers to present data in the form of numbers, graphs, or tables, making it easier to understand and analyze. With this method, researchers can provide a more accurate picture of the phenomenon being studied, as the data obtained is measured objectively. Data will be collected using surveys. The characteristics of entrepreneurs that will be asked of the respondents refer to the characteristics of 21st-century entrepreneurs, which include: the ability to recognize and seize opportunities; possessing a diverse range of skills; being creative; having future aspirations; thinking freely; being hardworking; optimistic; being an innovator; being willing to take risks; and having a leadership spirit. Generation Z demonstrates promising potential in areas such as independent thinking and opportunity recognition, there is a need for greater support and development in leadership skills, risk-taking abilities, and future-oriented goal setting to better equip them for entrepreneurial success in the evolving landscape of the Industrial Revolution 5.0. These insights suggest that while Gen Z exhibits promising traits for entrepreneurship, further support in leadership and future-oriented thinking could enhance their readiness to thrive in the evolving industrial revolution 5.0 landscape.